The effect of heat treatment on the morphology and mobility of Au nanoparticles - Oras, Sven; Vlassov, Sergei; Vigonski, Simon; Polyakov, Boris; Antsov, Mikk; Zadin, Vahur; Lõhmus, Rünno; Mougin, Karine (Beilstein-Institut Zur Forderung der Chemischen Wissenschaften, 2020)
In the present paper, we investigate the effect of heat treatment on the geometry and mobility of Au nanoparticles (NPs) on a Si substrate. Chemically synthesized Au NPs of diameter ranging from 5 to 27 nm were annealed at 200, 400, 600 and 800 °C for 1 h. A change in the geometry from faceted to more rounded shapes were observed with increasing annealing temperature. Kinetic Monte Carlo simulations indicate that the NPs become rounded due to the minimization of the surface area and the transition to lower energy surface types (111) and (100). The NPs were manipulated on a silica substrate with an atomic force microscope (AFM) in tapping mode. Initially, the NPs were immovable by AFM energy dissipation. However, annealed NPs became movable, and less energy was required to displace the NPs annealed at higher temperature. However, after annealing at 800 °C, the particles became immovable again. This effect was attributed to the diffusion of Au into the Si substrate and to the growth of the SiO2 layer.
This work was supported by The Centre National de la Recherche Scientifique (CNRS) of France and the French Embassy Program. The authors are also grateful for partial support by COST Action CA15216, the Estonian Science Foundation (grants PUT1689 and PUT1372), the Estonian Centre of Excellence in Zero Energy and Resource Efficient Smart Buildings and Districts, ZEBE, grant 2014-2020.4.01.15.0016 and Latvian Science Council grant lzp-2018/2-0083.
Keywords: Annealing; Atomic force microscopy (AFM); Au nanoparticles; Manipulation; Melting; Nanotribology; Research Subject Categories::NATURAL SCIENCES:Physics